ダイ 12 ジ ナンキョク チイキ カンソクタイ ナツタイ ホウコク 1970 1971 ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 村越, 望; ムラコシ, ノゾミ; MURAKOSHI, Nozomi (国立極地研究所, 1973)
P(論文) Forty members of the 12th Japanese Antarctic Research Expedition left Tokyo on November 25, 1970, aboard the icebreaker FUJI, under the command of Captain Masato OMORI. The expedition was led by Dr. Takasi OGUTI, also leading the wintering party consisting of 30 men, and the author, as deputy leader, led the summer party of 10 men. The FUJI carried 500 tons of cargo, including a single-engine monoplane Lockheed LASA-60, and was equipped with two Sikorsky S61-A helicopters and one Bell 47G2A helicopter. On December 16, the FUJI left Fremantle for Syowa Station and proceeded to pack ice off the coast of the Enderby Land. On January 10, 1971, one blade of starboard screw of Fuji was broken by very close pack ice and she was beset at 67°15.7'S, 44°48. 5'E (170 nautical miles northeast of Syowa Station) until February 10. On January 20, LASA, escorted by S-61 helicopter, started for Syowa Station, and after about 2 hours it landed at the destination. Three days after, LASA picked up the traverse party at F-16 that is the terminal point of our continent traverses. Early in February, the ice condition began to loosen. On February 10, the ship freed herself from heavy pack ice and advanced westward. On that night she reached 44 miles north of Syowa Station. On the next day, the first helicopter flight was made to transport men and cargo. Air transport was continued until March 16, and about 465 tons of cargo was landed. On account of the ship's besetting and delay in schedule, our summer programmes were largely changed. Cargoes of heavy weight or long size could not be carried by helicopter, because the rocket launching dome and the living hut were not constructed yet. From March 6 to 12, two field parties were sent by helicopter to the Lang Hovde area for the study of glaciology, biology and geochemistry. On March 16, the FUJI took a course to the north. After staying at Cape Town from March 29 to April 3, the FUJI returned to Tokyo on May 4. departmental bulletin paper